The Effect of Positive Self-Talk on Anxiety Levels in Hypertensive Patients in the Limboto Health Center Area - Meylan Batara; Nurdiana Djamaluddin; Mihrawaty S. Antu (Universitas Muhammadiyah Palu, 2026)
Hypertensive patients not only experience physical problems, but also psychological problems related to anxiety related to their illness. This anxiety is an independent risk factor that can worsen the condition of hypertensive patients. Pharmacological therapies such as psychopharmaceutical therapy and somatic therapy. The non-pharmacological therapies are deep breath relaxation therapy, distraction therapy, five-finger hypnosis therapy, murrotal Quran therapy, and positive self-talk therapy. Of these therapies, positive self-talk therapy is a therapy that is universal, easy to practice, and has a significant therapeutic effect in anxiety management in hypertensive patients. This study aims to determine the effect of positive-self-talk on the level of anxiety in hypertensive patients in the Limboto Health Center Area. The research design used in this study is a pseudo-experimental experiment or quasi-experimental non-equivalent control group design.The number of samples in this study was 36 respondents using purposive sampling. The results of the study using the Paired Sample T-Test showed that there was a positive effect of self-talk on the level of anxiety in hypertensive patients before and after being given intervention in the experimental group and control group in the Limboto Health Center area with a p-value of 0.000 (< 0.05) in the experimental group and a p-value result(0.825 (> 0.05) in the control group. It is hoped that this research can encourage hypertensive patients to be able to manage anxiety